Siklus Akuntansi Sektor Publik Pada Partai Nasional Demokrat - Addriansyah, Muhammad; Putri, Kanaya Malika; Alviandy, Devin; Firstania, Alisya Gadis; Anjani, Vanessa; Ananda, Della Rizky (Universitas Pembangunan Nasional Veteran Jakarta, 2024)
This research examines documents regarding the Public Sector Accounting Cycle Proposal in the National Democratic Party. In this era of dynamic economic progress and the need for transparency, understanding the public sector accounting cycle is very important. Through a survey conducted at the DPW residence, NASDEM involved steps such as budget planning, recording financial transactions, financial reporting and auditing. This is important to ensure transparency and accountability in the management of public funds.